Psychological Nursing of Patients With Stroke in China: A Systematic Review and Meta-Analysis - Liao, Bingye; Liang, Minni; Ouyang, Qiuyi; Song, Hongqin; Chen, Xiaojun; Su, Yuejiao (Frontiers in Psychiatry, 2020)
The present study aimed to evaluate the efficacy of psychological nursing of patients with stroke in China. The Embase, PubMed, Cochrane Library, CNKI, and Wanfang databases were searched from inception to February 1, 2020. Randomized controlled trials (RCTs) reporting the efficacy of psychological nursing of patients with stroke were included. Revman 5.3 and Stata 15.0 were used for data analysis. Twelve RCTs and 1013 patients with stroke were included in this systematic review and meta-analysis. The results revealed a significant difference in the Hamilton depression score between the psychological nursing and usual care groups. The meta-analysis of three studies (n=235) that used depressive symptom control ≥25% as the outcome measure showed a significant difference between the two groups. In addition, significant differences were detected in the National Institute of Health stroke scale score and activities of daily living score between the two groups. The present meta-analysis suggests that in China, compared to the usual care, psychological nursing is more effective for alleviating depressive symptoms, improving neurological rehabilitation, and recovering the ability of daily life.